Recruitment, development, and retention of information professionals : trends in human resources and knowledge management - Pankl, Elisabeth, 1975-; Theiss-White, Danielle, 1977-; Bushing, Mary. (Hershey, PA : Business Science Reference, 2010)
'This book offers disparate yet important perspectives of various information professionals pertaining to recruitment, retention and career development of individuals within organizations'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Academic libraries -- United States -- Personnel management; Academic librarians -- Recruiting -- United States; Academic librarians -- Training of -- United States; Knowledge workers -- Recruiting -- United States; Knowledge workers -- Training of -- United States; College personnel management -- United States; Knowledge management -- United States; Library education -- United States